Edukasi Berbasis Audio Visual Meningkatkan Tingkat Pengetahuan Remaja Tentang Pencegahan HIV/AIDS - Soffinda Nur Solikhah; Etty Eriyanti; Fajar Alam Putra (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Adolescents are a group that is vulnerable to HIV/AIDS transmission due to limited knowledge and high exposure to risky behaviors. Efforts to improve knowledge through engaging media are needed so that health messages can be optimally received. This study aimed to determine the effect of audiovisual-based education on adolescents’ level of knowledge regarding the prevention of HIV/AIDS transmission. This study employed a quasi-experimental design with a pretest–posttest control group approach. The research sample consisted of 76 respondents, divided into an intervention group and a control group, with 38 respondents in each group. The sampling technique used was proportionate stratified random sampling based on class or grade level. The research instrument was an HIV/AIDS knowledge questionnaire that had been tested for validity and reliability. The intervention was delivered in the form of an educational video with a duration of approximately 10–15 minutes. Data analysis was conducted using the marginal homogeneity test and the Kolmogorov–Smirnov test because the data were measured on an ordinal scale. The results showed an increase in the level of knowledge in the intervention group after receiving audiovisual education, with a p-value of 0.000 (p < 0.05). In contrast, no significant difference was found in the control group, with a p-value of 1.000 (p > 0.05). It can be concluded that audiovisual-based education has a significant effect on increasing adolescents’ knowledge regarding the prevention of HIV/AIDS transmission. Audiovisual media can be used as an alternative health education method for adolescents.